The Effect of Capital Adequacy on Return on Investment: A Study based on Commercial Banks in Bangladesh (Global Journal of Management and Business Research, 2019)
The main purpose of study was to establish the effect that capital adequacy have on the investments. It also found at how this capital adequacy was involved in other variables such as liquidity, management efficiency, asset quality and operating efficiency. Side by side, it found at whether other variables had a role to play in the investments. In this study, the collected data were applied in empirical analysis with regression analysis to analysis. A random sample from the population of total commercial bank in Bangladesh was taken as secondary sources of data from financial statement. A linear regression model of the returns on investments versus capital adequacy, liquidity, management efficiency, asset quality, operating efficiency was to test relationship among the variables. The results established that the relationship between capital adequacy of commercial banks and return on investment is negative and significant. The study found that capital adequacy had a negative effect on return on investments while liquidity had a positive impact on the returns. For this negative effect of capital adequacy on the returns in investment, the study recommends that a central depository fund for commercial Banks be set up to assist Banks have cheaper way for short term borrowing to useful to temporary liquidity crisis.
Keywords: ROI; CAR; NPL; core capital; deposits; central deposits